Oxidative Marker and Insulin Resistance in Women with PCOS - Saadia Zainab, Tayyaba Batool, Samia Sarwar, Iram Qamar, Noor-Ul-Ain, Qurat-Ul-Ain, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Polycystic Ovary Disorder may be a multifactorial reproductive issue and a leading cause of female infertility around the world. Confirmations have appeared that Oxidative Stress and diminished antioxidant status are often connected with PCOS. Oxidative stretch (OS) which plays a key part within the pathogenesis of CVD has also been documented in obese women with PCOS. Oxidative stress may have a part within the pathophysiology of PCOS and impact female reproductive system leading to infertility but the exact cause of OS in PCOS isn't totally understood. Objective: To determine the levels of Glucose, Malondialdehyde, serum insulin and insulin resistance in non-obese and obese PCOS women. Material and Methods Study design: Case Control Settings: Lady Atchison Hospital Lahore Duration: Six months i.e. 1st January 2021 to 30th June 2021 Data Collection procedure: Case control study was conducted to analyzed 100 PCOS patients and 100 controls. Fasting plasma glucose was measured. Insulin resistance was calculated by HOMA-IR. Malonaldehyde is determined as Thiobarbituric corrosive reactive substances Insulin was assessed by chemiluminescent microparticle immunoassay. Results: The levels were higher of serum glucose in both obese and non-obese PCOS patients. Serum levels of insulin in obese PCOS patients were high as compared to non-obese PCOS patient. The level of CRP is in the higher side in PCOS patients whether obese or non-obese when it compared to control ones. The level of MDA also on the higher side in PCOS patients whether obese or non-obese when it compared to control ones Conclusion: Within the present study, we found expanded oxidative stress and low review inflammation shown by raised levels of MDA and CRP in ladies with polycystic ovary syndrome irrespective of obesity. They can be utilized as markers for women PCOS. In any case, the serum insulin levels and IR in non-obese patients with PCOS in spite of the fact that expanded in connection to BMI balanced controls, the values were inside the reference range.